THE PREVALENCE OF ANEMIA IN THE YOUTH INTEGRATED HEALTH SERVICE POST AT PANDAK HAMLET, YOGYAKARTA, INDONESIA - NUR AINI DJUNET; RIANA RAHMAWATI (JURNAL ILMIAH SIMANTEK, 2022)
Adolescents are assets of every country, especially young women. Essentially the future of a nation is in the women hands. Women play a crucial role in giving birth and educating the next generation. Adolescence is a phase of life before women enter adulthood and are ready to birth in the future. Anemia has short- and long-term effects for young women. The early detection of anemia in teenagers is needed, so the adverse effects of anemia can prevent. The anemia prevalence of Indonesian adolescents increased 14% for five years. The population-based anemia data was limited. Teenagers are unique individuals; they want special handling as well. The youth forums to accommodate their various problems or aspirations are necessary. The Indonesian government established youth integrated health service post (YIHSP) to facilitate youth in the health sector. We aimed to determine the population-based prevalence of anemia. It was a cross-sectional study conducted in October 2021 at Yogyakarta, Indonesia, population was 83 female teenagers. Participants' height and weight were measured using a stadiometer and digital weighing scale, the capillary blood from the third finger was used to measure hemoglobin. There were 72% participants enrolled in this screening, 22% were anemic, 39% had normal nutritional status.